Spatiotemporal dynamics of soil erosion in the Daqing river basin: a comparative analysis of mountains and plains - Wang, Meng; Ding, Yuanyuan; Wang, Yong; Liu, Miao; Han, Xueli; Luan, Zhihao (Frontiers in Environmental Science, 2025)
Soil erosion has been significantly exacerbated by climate change and urbanization, posing serious threats to environmental protection and sustainable development. In this study, soil erosion in the Daqing River Basin from 2000 to 2022 was assessed using the revised universal soil loss equation (RUSLE) model, which incorporates data from digital elevation model (DEM), normalized vegetation index (NDVI), and land-use sources, and the spatiotemporal evolution of soil erosion was subsequently analyzed. The impacts of natural and anthropogenic factors on erosion and their interactions with soil erosion were analyzed via random forest and partial least squares-structural equation modeling (PLS-SEM). The results revealed that soil erosion in the Daqing River Basin averaged 159 t/(km2·a) from 2000 to 2022, with averages of 386 t/(km2·a) in the mountains and 1.1 t/(km2·a) in the plains. The erosion intensity increased from southeast to northwest, with higher levels in mountains than in plains. The soil erosion level initially improved but then deteriorated sharply after a significant turning point in 2015. Natural factors, particularly precipitation, were the largest drivers of soil erosion throughout the Daqing River Basin, whereas anthropogenic factors had the greater impact on erosion in plains than in mountains. There was strong synergy among various anthropogenic factors throughout the basin. In the mountains, anthropogenic factors were antagonistic to vegetation coverage, whereas in the plains, they were synergistic with vegetation coverage and meteorological factors.